Acetonitrile wastewater treatment enhanced by a hybrid membrane-aerated bioreactor containing aerated and non-aerated zones. (October 2019) - Mei, Xiang; Chen, Ying; Fang, Chenhong; Xu, Lijie; Li, Junhui; Bi, Shuqi; Liu, Juan; Wang, Yong; Li, Pengpeng; Guo, Zhongwei; Qin, Hailing; Gu, Jiawei; et al.
Graphical abstract: Highlights: A membrane-aerated bioreactor (MAB) with aerated and non-aerated zones was constructed. HF-MAB and SR-MAB were used to enhance acetonitrile (ACN) wastewater treatment. Two zones synergistically promoted ACN degradation, nitrification and denitrification. HF-MAB achieved an ACN removal loading of 1.116 kg/m 3 ·d without secondary pollution. The performances of the HF-MAB were slightly better than those of the SR-MAB. Abstract: Acetonitrile (ACN) is a very volatile, toxic and nitrogen-rich organic compound. To enhance ACN wastewater treatment, a novel hybrid membrane-aerated bioreactor (MAB) containing aerated and non-aerated zones was established. A polypropylene hollow fiber membrane module (HF) and a silicone rubber membrane module (SR) were separately used as the bubble-free aeration diffuser and the biofilm carrier, and the non-aerated zones of these two types of reactors were packed with ceramsite. When the influent ACN loading was 1.200 kg/m 3 ·d, under aeration pressures of 20 kPa in the HF-MAB and 40 kPa in the SR-MAB, ACN removal loadings of 1.116 kg/m 3 ·d and 1.004 kg/m 3 ·d, respectively, were achieved, and the TN (total nitrogen) removal loadings were 0.267 kg/m 3 ·d and 0.246 kg/m 3 ·d, respectively. In the MABs, different stratified biofilm structures of the two zones and the diffusion and counter-diffusion of oxygen synergistically promoted ACN degradation, nitrification and denitrification.